Polymer electrolyte, solid-state lithium metal battery and preparation method of solid-state lithium metal battery

By using a polymer electrolyte modified with a liquid ring ether complexing agent in lithium metal batteries, the problems of instability and safety hazards of traditional electrolyte interfaces are solved, and efficient lithium ion transmission and stable battery performance are achieved.

CN119852512AInactive Publication Date: 2025-04-18浙江冠盛东驰能源科技有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510024563.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The side reaction between traditional liquid electrolytes and lithium metal anodes leads to unstable interfaces of electrode electrolytes, and the highly flammable organic electrolytes increase the safety hazards of lithium metal batteries.

Method used

The polymer electrolyte containing a liquid ring ether complex is used to weaken the coupling of the polar groups of the polymer with the Lewis basic site of the lithium ions, improve the ion transfer speed, and generate a stable solid electrolyte interface through the cationic ring-opening reaction.

Benefits of technology

It realizes a high number of lithium ion migrations, a wide electrochemical window and a polymer electrolyte that is stable to the lithium negative electrode, which improves the critical current density and long cycle stability of solid-state lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852512A_ABST
    Figure CN119852512A_ABST
Patent Text Reader

Abstract

The invention provides a polymer electrolyte, a solid-state lithium metal battery and a preparation method of the solid-state lithium metal battery, and belongs to the field of lithium ion batteries. The invention provides a polymer electrolyte. The polymer electrolyte comprises a polymer, a liquid cyclic ether coordination agent dispersed in the polymer and a complex formed by lithium ions and the liquid cyclic ether coordination agent. The functional characteristic of coordination of the liquid cyclic ether coordination agent is utilized to coordinate with lithium ions, Lewis alkaline site coupling between polymer polar groups (such as carbonyl and nitrile groups) and the lithium ions is weakened, ion transmission of the polymer electrolyte is improved, the transmission effect of the lithium ions in the electrolyte is accelerated, concentration polarization is reduced, and the electrolyte performance is improved. The growth of lithium dendrites is inhibited; on the other hand, the liquid cyclic ether coordination agent is in contact with the lithium metal to generate a cationic ring-opening reaction to generate typical ROLi which is used as a firm and stable SEI to maintain the stability of the electrolyte and the lithium metal interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a polymer electrolyte, a solid-state lithium metal battery and a preparation method thereof. Background Art

[0002] With the rapid development of the new energy vehicle industry, the production of high energy density and high safety power batteries has become an unremitting goal in this field. Lithium metal has a low reduction potential (-3.040V relative to the standard hydrogen electrode) and a high theoretical specific capacity (3860mAh g -1 ), applied to the negative electrode material of power batteries can greatly improve the energy density of batteries. Therefore, lithium metal batteries are considered to be one of the most promising next-generation rechargeable batteries.

[0003] The side reactions between traditional liquid electrolytes and lithium metal anodes lead to unstable electrode-electrolyte interfaces. In addition, highly flammable organic electrolytes also exacerbate the safety risks of lithium metal batteries. However, solid polymer electrolytes, due to their immobility and chemical stability, can solve the safety problems of lithium batteries caused by electrolyte leakage and become the most promising lithium metal electrolytes. Matching high-capacity cathode materials and lithium metal anodes with solid electrolytes is expected to become the next generation of energy storage systems.

[0004] However, in conventional polymer electrolytes, Li + Usually strongly coupled to the Lewis basic sites of the polymer, resulting in Li + The transport is slow, usually slower than that of anions, which inevitably produces lithium dendrites caused by concentration polarization, hindering the practical application of high-energy-density solid-state lithium metal batteries. Summary of the invention

[0005] The present invention provides a polymer electrolyte, a solid-state lithium metal battery and a preparation method thereof. The polymer electrolyte of the present invention has high room temperature ionic conductivity, a large lithium ion migration number, a wide electrochemical window and excellent stability to lithium; a solid-state lithium battery containing the polymer electrolyte has high critical current density and good long cycle stability.

[0006] The invention provides a polymer electrolyte, comprising a polymer, a liquid cyclic ether coordination agent dispersed in the polymer, and a complex formed by lithium ions and the liquid cyclic ether coordination agent.

[0007] A polymer electrolyte comprises a polymer, a liquid cyclic ether coordination agent dispersed in the polymer, and a complex formed by lithium ions and the liquid cyclic ether coordination agent.

[0008] Preferably, the raw materials for preparing the polymer electrolyte include:

[0009] Organic lithium salt, inorganic lithium salt, cross-linking agent, monomer having functional groups and double bonds, liquid cyclic ether coordination agent and thermal initiator;

[0010] The functional groups include one or more of carbonyl, cyano, amide and ester groups.

[0011] Preferably, the organic lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) and lithium difluorooxalatoborate;

[0012] The inorganic lithium salt includes lithium nitrate.

[0013] Preferably, the ratio of the mass of the organic lithium salt to the total mass of the comonomer and the crosslinking agent is (2-4.5):10;

[0014] The ratio of the mass of the inorganic lithium salt to the total mass of the polymonomer and the cross-linking agent is (2-4.5):100.

[0015] Preferably, the crosslinking agent preferably includes one or more of tris(2-acryloyloxyethyl)isocyanurate (containing stabilizer phenothiazine), ethoxylated trimethylolpropane triacrylate, polyethylene glycol dimethacrylate and polyethylene glycol methyl ether methacrylate.

[0016] Preferably, the monomer includes one or more of vinyl ethylene carbonate, vinyl ethyl carbonate, methyl methacrylate, trifluoroethyl methacrylate, acrylonitrile, 3-aminocrotononitrile, cinnamonitrile and acrylamide.

[0017] Preferably, the mass ratio of the monomer to the cross-linking agent is (2-6):1.

[0018] Preferably, the liquid cyclic ether complexing agent includes one or more of tetrahydrofuran, 1,3-dioxolane, 2-methoxy-1,3-dioxolane and 1,3,5-trioxane.

[0019] The present invention also provides a solid-state lithium metal battery, comprising the polymer electrolyte described in the above technical solution.

[0020] The present invention also provides a method for preparing the solid-state lithium metal battery described in the above technical solution, comprising the following steps:

[0021] The raw materials for preparing the polymer electrolyte described in the above technical solution are mixed and poured into the diaphragm of the solid-state battery, and then assembled with other components of the solid-state battery to perform a polymerization reaction to generate a polymer electrolyte, thereby obtaining the solid-state battery.

[0022] The present invention utilizes the functional characteristics of the liquid cyclic ether ligand to coordinate the lithium salt, weaken the Lewis basic site coupling between the polymer polar groups (such as carbonyl and nitrile groups) and lithium ions, improve the ion transport of the polymer electrolyte, accelerate the transmission of lithium ions in the electrolyte, reduce concentration polarization, and inhibit the growth of lithium dendrites; on the other hand, the liquid cyclic ether ligand contacts lithium metal to generate a typical ROLi cationic ring-opening reaction, which serves as a strong and stable SEI to maintain the stability of the electrolyte and lithium metal interface. Therefore, the polymer electrolyte of the present invention is a coordinated polymer electrolyte with a high lithium ion migration number, a wide electrochemical window, and stability to the lithium negative electrode, which makes the assembled ternary positive electrode|polymer electrolyte|Li battery show excellent cycle stability and high capacity utilization. The results of the embodiment show that the room temperature conductivity of the coordinated polymer electrolyte prepared by the present invention is as high as 2.25×10 -4 S cm -2 , lithium ion migration number is 0.7, electrochemical window is 4.7V, critical current density is 2.268mAcm -2 , and has a stable electrode / electrolyte interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the SEM image of the PP diaphragm in Example 1;

[0024] Figure 2 is a SEM image of the polymer electrolyte of Example 1;

[0025] Figure 3 This is the electrochemical window diagram of the polymer electrolyte of Example 1;

[0026] Figure 4 It curve of the Li / Li symmetrical battery assembled in Example 1 and impedance diagram before and after battery polarization;

[0027] Figure 5 Cyclic test diagram of NCM811 / Li battery assembled with the combination of coordinated coordination polymer electrolyte and separator prepared in situ in Example 1 and Comparative Example 1;

[0028] Figure 6 This is a comparison chart of the long cycle of button batteries assembled in Example 1 and Comparative Example 1 at 4.3V and 0.5C;

[0029] Figure 7 The long cycle performance diagram of the NCM811 / Li battery assembled with the coordinated coordination polymer electrolyte prepared in Example 1 at 2C;

[0030] Figure 8The long cycle performance diagram of the NCM811 / Li battery assembled with the coordinated coordination polymer electrolyte prepared in Example 1 at 4.5V;

[0031] Fig. 9 The voltage variation curve of the Li / / Li symmetric battery assembled with the coordinated coordination polymer electrolyte prepared in Example 1 at constant current over time;

[0032] Fig.10 The voltage variation curve of the Li / / Li symmetric battery assembled with the coordinated coordination polymer electrolyte prepared in Comparative Example 1 at constant current over time;

[0033] Fig.11 Critical current density of Li / / Li symmetric cells assembled with coordinated coordination polymer electrolytes prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0034] The invention provides a polymer electrolyte, comprising a polymer, a liquid cyclic ether coordination agent dispersed in the polymer, and a complex formed by lithium ions and the liquid cyclic ether coordination agent.

[0035] In the present invention, the raw materials for preparing the polymer electrolyte preferably include organic lithium salts.

[0036] In the present invention, the ratio of the mass of the organic lithium salt to the total mass of the monomer and the cross-linking agent is preferably (2-4.5):10. In a specific embodiment of the present invention, the ratio of the mass of the organic lithium salt to the total mass of the monomer and the cross-linking agent can be 2:10, 2.1:10, 2.2:10, 2.3:10, 2.4:10, 2.5:10, 2.6:10, 2.7:10, 2.8:10, 2.9:10, 3: 10, 3.1:10, 3.2:10, 3.3:10, 3.4:10, 3.5:10, 3.6:10, 3.7:10, 3.8:10, 3.9:10, 4:10, 4.1:10, 4.2:10, 4.3:10, 4.4:10 or 4.5:10; the organic lithium salt preferably includes one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) and lithium difluorooxalatoborate.

[0037] In the present invention, the raw materials for preparing the polymer electrolyte preferably include organic lithium salts.

[0038] The ratio of the mass of the inorganic lithium salt to the total mass of the monomer and the cross-linking agent is preferably (2-4.5):100. In a specific embodiment of the present invention, the ratio of the mass of the inorganic lithium salt to the total mass of the monomer and the cross-linking agent can be 2:10, 2.1:100, 2.2:100, 2.3:100, 2.4:100, 2.5:100, 2.6:100, 2.7:100, 2.8:100. The inorganic lithium salt preferably comprises lithium nitrate. The present invention limits the ratio of the mass of the inorganic lithium salt and the organic lithium salt to the total mass of the monomer and the cross-linking agent within the above range, which can provide good ionic conductivity and a stable electrode electrolyte interface.

[0039] In the present invention, the raw materials for preparing the polymer electrolyte preferably include a crosslinking agent; the crosslinking agent preferably includes one or more of tris(2-acryloxyethyl)isocyanurate (containing stabilizer phenothiazine), ethoxylated trimethylolpropane triacrylate, polyethylene glycol dimethacrylate and polyethylene glycol methyl ether methacrylate; the structural formulas of tris(2-acryloxyethyl)isocyanurate (containing stabilizer phenothiazine), ethoxylated trimethylolpropane triacrylate, polyethylene glycol dimethacrylate and polyethylene glycol methyl ether methacrylate are shown in (1) to (4).

[0040]

[0041] In the present invention, the raw materials for preparing the polymer electrolyte preferably include monomers having functional groups and double bonds, and the functional groups preferably include one or more of carbonyl, cyano, amide and ester groups; the monomers preferably include one or more of vinyl ethylene carbonate (structural formula shown in I), vinyl ethyl carbonate (structural formula shown in II), methyl methacrylate (structural formula shown in III), trifluoroethyl methacrylate (structural formula shown in IV), acrylonitrile (structural formula shown in V), 3-aminocrotononitrile (structural formula shown in VI), cinnamonitrile (structural formula shown in VII) and acrylamide (structural formula shown in VIII).

[0042]

[0043] In the present invention, the mass ratio of the monomer to the cross-linking agent is preferably (2-6):1. In a specific embodiment of the present invention, the mass ratio of the monomer to the cross-linking agent can be 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1 :1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1, 5:1, 5.1:1, 5.2:1, 5.3:1, 5.4:1, 5.5:1, 5.6:1, 5.7:1, 5.8:1, 5.9:1 or 6:1. In a specific embodiment of the present invention, the monomers may be vinyl ethylene carbonate and acrylonitrile; the mass ratio of the vinyl ethylene carbonate to the cross-linking agent may be 3 to 4:1, the mass ratio of the vinyl ethylene carbonate to the cross-linking agent may be 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1 or 4:1, and the mass ratio of the acrylonitrile to the cross-linking agent may be The mass ratio of acrylonitrile to the crosslinking agent may be (0.5-2.5):1, and the mass ratio of acrylonitrile to the crosslinking agent may also be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1.

[0044] The present invention limits the mass ratio of the crosslinking agent to the monomer within the above range, which can effectively improve the mechanical strength of the polymer electrolyte skeleton.

[0045] In the present invention, the raw material for preparing the polymer electrolyte preferably includes a liquid cyclic ether ligand, and the liquid cyclic ether ligand preferably includes one or more of tetrahydrofuran (THF), 1,3-dioxolane, 2-methoxy-1,3-dioxolane and 1,3,5-trioxane (TEX). The liquid cyclic ether ligand can react with Li + Coordination occurs, weakening Li + The strong coordination effect with the polar groups in the polymer skeleton accelerates the transmission of lithium ions, optimizes the lithium ion transmission path, and avoids the formation of dendrites.

[0046] In the present invention, the ratio of the mass of the liquid cyclic ether complexing agent to the total mass of the monomer and the cross-linking agent is preferably (2.2-5.5):10. In a specific embodiment of the present invention, the ratio of the mass of the liquid cyclic ether complexing agent to the total mass of the monomer and the cross-linking agent can be 2.2:10, 2.3:10, 2.4:10, 2.5:10, 2.6:10, 2.7:10, 2.8:10, 2.9:10, 3:10, 3.1:10, 3.2: : 10, 3.3:10, 3.4:10, 3.5:10, 3.6:10, 3.7:10, 3.8:10, 3.9:10, 4:10, 4.1:10, 4.2:10, 4.3:10, 4.4:10, 4.5:10, 4.6:10, 4.7:10, 4.8:10, 4.9:10, 5:10, 5.1:10, 5.2:10, 5.3:10, 5.4:10, or 5.5:10.

[0047] In the present invention, the raw materials for preparing the polymer electrolyte preferably include a thermal initiator; the thermal initiator includes an azo thermal initiator and / or a peroxide thermal initiator; the azo thermal initiator preferably includes 2-2-azobisisobutyronitrile, and the peroxide thermal initiator preferably includes benzoyl peroxide.

[0048] In the present invention, the ratio of the mass of the thermal initiator to the total mass of the cross-linking agent and the monomer is preferably (1-2):100. In a specific embodiment of the present invention, the ratio of the mass of the thermal initiator to the total mass of the cross-linking agent and the monomer can be 1:100, 1.1:100, 1.2:100, 1.3:100, 1.4:100, 1.5:100, 1.6:100, 1.7:100, 1.8:100, 1.9:100 or 2:100.

[0049] The present invention limits the ratio of the mass of the thermal initiator to the total mass of the crosslinking agent and the monomer within the above range, which enables a better crosslinking reaction to occur, thereby generating a polymer electrolyte skeleton with a wide electrochemical window, a high dielectric constant and certain mechanical properties.

[0050] The present invention also provides a solid-state lithium metal battery, which is composed of a battery positive electrode buckle, a positive electrode, the polymer electrolyte described in the above technical solution, a lithium sheet, a gasket, a spring and a battery negative electrode buckle.

[0051] The present invention also provides a method for preparing a solid-state lithium metal battery, comprising the following steps:

[0052] The raw materials for preparing the polymer electrolyte described in the above technical solution are mixed and injected into the diaphragm of the solid-state battery, and then assembled with other components of the solid-state battery, and then subjected to polymerization reaction to obtain the solid-state battery.

[0053] In the present invention, the mixing preferably includes first mixing the lithium salt, the cross-linking agent, the monomer and the liquid cyclic ether complexing agent to obtain a raw material premix liquid;

[0054] The raw material premix liquid and the thermal initiator are mixed for the second time.

[0055] In the present invention, the first mixing is preferably carried out under stirring conditions; the stirring is preferably mechanical stirring; the stirring speed is preferably 200-500 rpm; the stirring time is preferably 4-6 hours; and the stirring temperature is preferably 20-30°C.

[0056] In the present invention, the second mixing is preferably carried out under stirring conditions; the stirring is preferably mechanical stirring; the stirring speed is preferably 300-500 rpm; the stirring temperature is preferably 30-40° C., and the stirring time is preferably 1 hour.

[0057] The present invention limits the rotation speed, temperature and time of stirring in the first mixing and the second mixing to the above ranges, so that the components can be mixed more evenly.

[0058] After the injection, the present invention preferably allows the mixture obtained by mixing to stand.

[0059] The present invention has no particular limitation on the standing still process, and a conventional solution may be adopted to allow the mixture to fully infiltrate the diaphragm.

[0060] In the present invention, the material of the diaphragm preferably includes PE or PP.

[0061] In the present invention, the volume of the mixture injected into the diaphragm is preferably 50 to 60 μL.

[0062] In the present invention, the polymerization reaction temperature is preferably 40-60°C. In a specific embodiment of the present invention, the polymerization reaction temperature may be 40°C, 45°C, 50°C, 55°C or 60°C. The polymerization reaction time is preferably 6-12h. In a specific embodiment of the present invention, the polymerization reaction time may be 6h, 7h, 8h, 9h, 10h, 11h or 12h.

[0063] In the present invention, during the thermal polymerization process, the rigid crosslinking agent and the thermal reactant undergo a free radical crosslinking reaction under the action of the thermal initiator.

[0064] The polymer electrolyte, solid-state lithium metal battery and preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0065] Example 1

[0066] (1) 0.0875 g of tris(2-acryloyloxyethyl)isocyanurate (containing phenothiazine as a stabilizer), 0.14 g of lithium bis(trifluoromethanesulfonyl)imide, 0.014 g of lithium nitrate, 0.285 g of vinyl ethylene carbonate, 76 μL of acrylonitrile and 0.125 g of 1,3,5-trioxane were mixed and stirred at 25° C. for 5 h to obtain a raw material premix solution;

[0067] (2) adding a crosslinking agent and 1% of the total weight of the monomers to 2-2-azobisisobutyronitrile, stirring at 40° C. and 300 r / min for 1 h to obtain a precursor solution;

[0068] (3) Inject 50 μL of the precursor solution into the PP diaphragm to assemble a button-type full battery. The battery is assembled in the order of positive electrode button, positive electrode, PP diaphragm, injection of precursor solution, lithium sheet, gasket, spring, and negative electrode button. After the precursor is injected, it is left to stand for 2 minutes to allow the precursor solution to fully infiltrate the diaphragm. The assembled battery is placed in an oven at 60°C for thermal polymerization for 12 hours. Finally, a coordinated coordination polymer electrolyte and a solid-state lithium metal battery (steel-to-steel button battery) containing the electrolyte are obtained in situ.

[0069] Alternatively, the battery positive electrode button, lithium sheet, PP separator, 50 μL precursor solution injection, lithium sheet, gasket, spring, and battery negative electrode button are assembled in this order and allowed to stand for 2 minutes after the precursor solution is injected to allow the precursor solution to fully infiltrate the separator. The battery is placed in a 60°C oven for thermal polymerization for 12 hours to obtain a Li / Li symmetrical battery.

[0070] Example 2

[0071] (1) 0.1312 g of tris(2-acryloyloxyethyl)isocyanurate (containing phenothiazine as a stabilizer), 0.14 g of lithium bis(trifluoromethanesulfonyl)imide, 0.014 g of lithium nitrate, 0.285 g of vinyl ethylene carbonate, 76 μL of acrylonitrile and 0.125 g of 1,3,5-trioxane were mixed and stirred at 25° C. for 5 h to obtain a raw material premix solution;

[0072] (2) adding a crosslinking agent and 1% of the total weight of the monomers to 2-2-azobisisobutyronitrile, stirring at 40° C. and 300 r / min for 1 h to obtain a precursor solution;

[0073] (3) Inject 50 μL of the precursor solution into the PP diaphragm to assemble a button-type full battery. The battery is assembled in the order of positive electrode button, positive electrode, PP diaphragm, injection of precursor solution, lithium sheet, gasket, spring, and negative electrode button. After the precursor is injected, it is left to stand for 2 minutes to allow the precursor solution to fully infiltrate the diaphragm. The assembled battery is placed in an oven at 60°C for thermal polymerization for 12 hours. Finally, a coordinated coordination polymer electrolyte and a solid-state lithium metal battery (steel-to-steel button battery) containing the electrolyte are obtained in situ.

[0074] Example 3

[0075] (1) 0.0875 g of tris(2-acryloyloxyethyl)isocyanurate (containing phenothiazine as a stabilizer), 0.14 g of lithium bis(trifluoromethanesulfonyl)imide, 0.014 g of lithium nitrate, 0.285 g of vinyl ethylene carbonate, 76 μL of acrylonitrile and 0.25 g of 1,3,5-trioxane were mixed and stirred at 25° C. for 5 h to obtain a raw material premix solution;

[0076] (2) adding a crosslinking agent and 1% of the total weight of the monomers to 2-2-azobisisobutyronitrile, stirring at 40° C. and 300 r / min for 1 h to obtain a precursor solution;

[0077] (3) Inject 50 μL of the precursor solution into the PP diaphragm to assemble a button-type full battery. The battery is assembled in the order of positive electrode button, positive electrode, PP diaphragm, injection of precursor solution, lithium sheet, gasket, spring, and negative electrode button. After the precursor is injected, it is left to stand for 2 minutes to allow the precursor solution to fully infiltrate the diaphragm. The assembled battery is placed in an oven at 60°C for thermal polymerization for 12 hours. Finally, a coordinated coordination polymer electrolyte and a solid-state lithium metal battery (steel-to-steel button battery) containing the electrolyte are obtained in situ.

[0078] Example 4

[0079] (1) 0.0875 g of tris(2-acryloyloxyethyl)isocyanurate (containing phenothiazine as a stabilizer), 0.14 g of lithium bis(trifluoromethanesulfonyl)imide, 0.014 g of lithium nitrate, 0.1425 g of vinyl ethylene carbonate, 76 μL of acrylonitrile and 0.125 g of 1,3,5-trioxane were mixed and stirred at 25° C. for 5 h to obtain a raw material premix solution;

[0080] (2) adding a crosslinking agent and 1% of the total weight of the monomers to 2-2-azobisisobutyronitrile, stirring at 40° C. and 300 r / min for 1 h to obtain a precursor solution;

[0081] 50 μL of the precursor solution was injected into the PP diaphragm to assemble the button-type full battery. The battery was assembled in the order of positive electrode button, positive electrode, PP diaphragm, injection of precursor solution, lithium sheet, gasket, spring, and negative electrode button. After the precursor was injected, it was left to stand for 2 minutes to allow the precursor solution to fully infiltrate the diaphragm. The assembled battery was placed in an oven at 60°C for thermal polymerization for 12 hours. Finally, a coordinated coordination polymer electrolyte and a solid-state lithium metal battery (steel-to-steel button battery) containing the electrolyte were obtained in situ.

[0082] Example 5

[0083] (3) 0.0875 g of tris(2-acryloyloxyethyl)isocyanurate (containing phenothiazine as a stabilizer), 0.14 g of lithium bis(trifluoromethanesulfonyl)imide, 0.014 g of lithium nitrate, 0.285 g of vinyl ethylene carbonate, 152 μL of acrylonitrile and 0.125 g of 1,3,5-trioxane were mixed and stirred at 25° C. for 5 h to obtain a raw material premix solution;

[0084] (4) adding a crosslinking agent and 1% of the total weight of the monomers to 2-2-azobisisobutyronitrile, stirring at 40° C. and 300 r / min for 1 h to obtain a precursor solution;

[0085] 50 μL of the precursor solution was injected into the PP diaphragm to assemble the button-type full battery. The battery was assembled in the order of positive electrode button, positive electrode, PP diaphragm, injection of precursor solution, lithium sheet, gasket, spring, and negative electrode button. After the precursor was injected, it was left to stand for 2 minutes to allow the precursor solution to fully infiltrate the diaphragm. The assembled battery was placed in an oven at 60°C for thermal polymerization for 8 hours. Finally, a coordinated coordination polymer electrolyte and a solid-state lithium metal battery (steel-to-steel button battery) containing the electrolyte were obtained in situ.

[0086] Comparative Example 1

[0087] (1) 0.0875 g of tris(2-acryloyloxyethyl)isocyanurate (containing phenothiazine as a stabilizer), 0.14 g of lithium bis(trifluoromethanesulfonyl)imide, 0.014 g of lithium nitrate, 0.285 g of vinyl ethylene carbonate, and 76 μL of acrylonitrile were mixed and stirred at 25° C. for 5 h to obtain a raw material premix solution;

[0088] (2) adding a crosslinking agent and 1% of the total weight of the monomers to 2-2-azobisisobutyronitrile, stirring at 40° C. and 300 r / min for 1 h to obtain a precursor solution;

[0089] (3) Inject 50 μL of the precursor solution into the PP diaphragm to assemble the button-type full battery. The battery positive electrode button, positive electrode, PP diaphragm, injection of the precursor solution, lithium sheet, gasket, spring, battery negative electrode button are assembled in the order of battery positive electrode button, and stand for 2 minutes after the precursor is injected to allow the precursor solution to fully infiltrate the diaphragm. The assembled battery is placed in an oven at 60°C for thermal polymerization for 12 hours. Finally, the coordinated coordination polymer electrolyte and the assembled lithium metal battery (steel-to-steel button battery) are obtained in situ.

[0090] Alternatively, the battery positive electrode button, lithium sheet, PP separator, 50 μL precursor solution injection, lithium sheet, gasket, spring, and battery negative electrode button are assembled in this order and allowed to stand for 2 minutes after the precursor solution is injected to allow the precursor solution to fully infiltrate the separator. The battery is placed in a 60°C oven for thermal polymerization for 12 hours to obtain a Li / Li symmetrical battery.

[0091] The impedance values ​​of the in-situ assembled steel-to-steel button cells of Examples 1 to 5 and Comparative Example 1 were measured, and the thickness of the electrolyte membrane was measured after disassembly. The room temperature conductivity of the polymer electrolytes of Examples 1 to 5 and Comparative Example 1 was calculated. The results are shown in Table 1.

[0092] Table 1 Room temperature conductivity of polymer electrolyte obtained in Examples 1 to 2

[0093] Room temperature conductivity Example 1 <![CDATA[2.25×10 -4 Scm -1 ]]> Example 2 <![CDATA[1.53×10 -4 Scm -1 ]]> Example 3 <![CDATA[2.77×10 -4 Scm -1 ]]> Example 4 <![CDATA[2.04×10 -4 Scm -1 ]]> Example 5 <![CDATA[1.12×10 -4 Scm -1 ]]> Comparative Example 1 <![CDATA[1.37×10 -4 Scm -1 ]]>

[0094] From the data in Table 1, it can be seen that the solid polymer electrolyte provided by the present invention has a high conductivity of 1.12×10 -4 ~2.77×10 -4 S cm -1 .

[0095] The SEM image of the PP diaphragm in Example 1 is as follows: Figure 1 As shown;

[0096] The SEM image of the in-situ prepared coordinated polymer electrolyte of Example 1 is as follows: Figure 2 shown.

[0097] Depend on Figures 1-2 It can be seen that the precursor solution can fully infiltrate and cover the pores in the PP separator.

[0098] Figure 3 This is the electrochemical window diagram of the coordinated coordination polymer electrolyte prepared in Example 1.

[0099] from Figure 3 It can be seen that the electrochemical window of the coordinated coordination polymer electrolyte prepared in Example 1 is increased to 4.7V, which can match the ternary positive electrode material.

[0100] Figure 4 It curve of the Li / Li symmetric battery assembled in Example 1 and impedance diagram before and after battery polarization.

[0101] from Figure 4 It can be seen that the lithium ion migration number of the coordinated coordination polymer electrolyte prepared in Example 1 is as high as 0.7 at room temperature.

[0102] The NCM811 / Li battery was assembled with the combination of the coordinated polymer electrolyte and the separator prepared in situ in Example 1 and Comparative Example 1. The positive electrode active material was positive electrode 811, the current collector was aluminum foil, the conductive agent was acetylene black, and the binder was polytetrafluoroethylene; the negative electrode was metallic lithium. The obtained NCM811 / Li battery was subjected to a rate cycle test. The results are as follows Figure 5 shown.

[0103] from Figure 5It can be seen that the discharge capacities at 0.1C, 0.2C, 0.5C, and 1C are 201.6, 186.5, 170.3, and 148.1 mAh g, respectively. -1 , showing excellent discharge capacity. This indicates that the button cell assembled with the coordinated coordination polymer electrolyte prepared in Example 1 has good electrochemical reversibility.

[0104] The long cycle performance of the NCM811 / Li battery assembled with the coordinated coordination polymer electrolyte prepared in Example 1 and the polymer electrolyte of Comparative Example 1 at 4.3V and 0.5C was tested. The results are as follows: Figure 6 shown.

[0105] from Figure 6 It can be seen that the capacity retention rate of the NCM811 / Li battery assembled with the coordinated coordination polymer electrolyte prepared in Example 1 is as high as 80% after 300 cycles at 0.5C, 66.6% after 400 cycles, and still 60% after 500 cycles; while the NCM811 / Li battery assembled with the polymer electrolyte of Comparative Example 1 exhibits obvious attenuation in the long cycle at 0.5C.

[0106] The long cycle performance of the NCM811 / Li battery assembled with the coordinated coordination polymer electrolyte prepared in Example 1 at 2C was tested. The results are as follows: Figure 7 shown.

[0107] from Figure 7 It can be seen that the NCM811 / Li battery assembled with the in-situ prepared coordinated coordination polymer electrolyte still has excellent long-term cycle stability at high rates.

[0108] The long cycle performance of the NCM811 / Li battery assembled with the coordinated coordination polymer electrolyte prepared in Example 1 at 4.5V was tested. The results are as follows: Figure 8 The NCM811 / Li battery assembled with the coordinated polymer electrolyte prepared as shown in the figure increases the cut-off voltage to 4.5 V, and it is found that the initial discharge capacity is increased from 188.84 mAh g -1 .

[0109] The voltage variation curves of the Li / Li symmetric battery assembled with the coordinated coordination polymer electrolyte prepared in Example 1 and the polymer electrolyte prepared in Comparative Example 1 under constant current conditions are as follows: Fig. 9 , 10 shown.

[0110] from Figures 9-10 It can be seen that at 0.5 mA cm -2Under the current density of , the polarization voltage curve of the Li / Li symmetric battery assembled by the coordinated coordination polymer electrolyte battery prepared in situ in Example 1 is relatively stable, and it can still stably cycle for 300 hours at a small overpotential; while the polarization voltage of the Li / Li symmetric battery assembled by the polymer electrolyte of Comparative Example 1 surges at 50 hours and then short-circuits, indicating that the polymer electrolyte in Comparative Example 1 is difficult to form a stable interface with lithium metal.

[0111] The critical current density of the Li / Li symmetric battery assembled with the coordinated coordination polymer electrolyte prepared in Test Example 1 and the polymer electrolyte prepared in Comparative Example 1 was tested. The results are as follows: Fig.11 The coordinated polymer electrolyte prepared in Example 1 has a high critical current density of 2.26 mA cm -2 , which is about three times that of the polymer electrolyte in Comparative Example 1.

[0112] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polymer electrolyte, characterized in that The invention comprises a polymer, a liquid cyclic ether coordination agent dispersed in the polymer, and a complex formed by lithium ions and the liquid cyclic ether coordination agent.

2. The polymer electrolyte according to claim 1, characterized in that The raw materials for preparing the polymer electrolyte include: Organic lithium salt, inorganic lithium salt, cross-linking agent, monomer having functional groups and double bonds, liquid cyclic ether coordination agent and thermal initiator; The functional groups include one or more of carbonyl, cyano, amide and ester groups.

3. The polymer electrolyte according to claim 2, characterized in that The organic lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) and lithium difluorooxalatoborate; The inorganic lithium salt includes lithium nitrate.

4. The polymer electrolyte according to claim 3, characterized in that The ratio of the mass of the organic lithium salt to the total mass of the polymonomer and the cross-linking agent is (2-4.5):10; The ratio of the mass of the inorganic lithium salt to the total mass of the polymonomer and the cross-linking agent is (2-4.5):

100.

5. The polymer electrolyte according to claim 2, characterized in that The crosslinking agent includes one or more of tris(2-acryloyloxyethyl)isocyanurate (containing phenothiazine as a stabilizer), ethoxylated trimethylolpropane triacrylate, polyethylene glycol dimethacrylate and polyethylene glycol methyl ether methacrylate.

6. The polymer electrolyte according to claim 2, characterized in that The monomers include one or more of vinyl ethylene carbonate, vinyl ethyl carbonate, methyl methacrylate, trifluoroethyl methacrylate, acrylonitrile, 3-aminocrotononitrile, cinnamonitrile and acrylamide.

7. The polymer electrolyte according to claim 2, 5 or 6, characterized in that The mass ratio of the monomer to the cross-linking agent is (2-6):

1.

8. The polymer electrolyte according to claim 1, characterized in that The liquid cyclic ether complexing agent includes one or more of tetrahydrofuran, 1,3-dioxolane, 2-methoxy-1,3-dioxolane and 1,3,5-trioxane.

9. A solid-state lithium metal battery, characterized in that: The invention comprises the polymer electrolyte according to any one of claims 1 to 9.

10. The method for preparing a solid-state lithium metal battery according to claim 9, characterized in that: The following steps are involved: The raw materials for preparing the polymer electrolyte according to any one of claims 1 to 9 are mixed and poured into the diaphragm of the solid-state battery, and then assembled with other components of the solid-state battery to perform a polymerization reaction to generate a polymer electrolyte, thereby obtaining the solid-state battery.

Citation Information

Patent Citations

  • High-voltage-resistant solid polymer electrolyte and preparation method thereof and lithium ion battery

    CN113929834A

  • Interface self-healing type polymer electrolyte as well as preparation method and application thereof

    CN116581378A

  • Salt-coated polymer solid electrolyte, preparation method thereof and lithium battery

    CN118398888A

  • Lithium secondary cell

    CN1291359A

  • Non-aqueous electrolytes for electrochemical cells

    CN1333933A